Incentive Pay Programs Do Not Affect Teacher Motivation or Reported Practices: Results From Three Randomized Studies. (March 2013) - Yuan, Kun; Le, Vi-Nhuan; McCaffrey, Daniel F.; Marsh, Julie A.; Hamilton, Laura S.; Stecher, Brian M.; Springer, Matthew G.
This study drew on teacher survey responses from randomized experiments exploring three different pay-for-performance programs to examine the extent to which these programs motivated teachers to improve student achievement and the impact of such programs on teachers' instruction, number of hours worked, job stress, and collegiality. Results showed that most teachers did not report their program as motivating. Moreover, the survey responses suggest that none of the three programs changed teachers' instruction, increased their number of hours worked or job stress, or damaged their collegiality. Future research needs to further examine the logic model of pay-for-performance programs and test alternative incentive models such as rewarding teachers based on their practices and job responsibilities rather than on student outcomes.